2017
DOI: 10.1103/physreva.95.020102
|View full text |Cite
|
Sign up to set email alerts
|

Unbounded randomness certification using sequences of measurements

Abstract: Unpredictability, or randomness, of the outcomes of measurements made on an entangled state can be certified provided that the statistics violate a Bell inequality. In the standard Bell scenario where each party performs a single measurement on its share of the system, only a finite amount of randomness, of at most 4 log 2 d bits, can be certified from a pair of entangled particles of dimension d. Our work shows that this fundamental limitation can be overcome using sequences of (nonprojective) measurements on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
146
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(149 citation statements)
references
References 22 publications
3
146
0
Order By: Relevance
“…This is a manifestation of the good quality of our device, which may find applications in random number generators [65][66][67]. Care must be taken, however, in extending these considerations to adversarial scenarios, when the presence of loopholes, either from fair sampling or from "clumsiness" of the experimenter [37,68], can play a role.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…This is a manifestation of the good quality of our device, which may find applications in random number generators [65][66][67]. Care must be taken, however, in extending these considerations to adversarial scenarios, when the presence of loopholes, either from fair sampling or from "clumsiness" of the experimenter [37,68], can play a role.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…The last equality is obtained by replacing the factor d by the sum over b i , then remarking that in the integral the index b i can be used to address any other column of U (since they play similar roles), and eventually to permute the sum and the integral to recover exactly Eq. (13). Interestingly, the steering properties of CSMUB have already been characterized [28].…”
Section: B Finite Sets Of Measurementsmentioning
confidence: 99%
“…Moreover, they showed that an arbitrary long sequence of Bobs can establish nonlocal correlations with Alice, given that their measurement inputs are judiciously biased. This motivated further work exploring the potential of these ideas for randomness generation [13] and their classical communication cost [14], and led to experimental demonstrations [15,16]. More recently, these ideas were extended to other types of quantum correlations [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Optimizing the choice of min-tradeoff function over F min is a non-convex and not necessarily continuous problem [60]. Our analysis in Sec.…”
Section: Resultsmentioning
confidence: 99%